Agronomical characterization of cacao accessions - Almeida, Caio Márcio Vasconcellos de; Dias, Luiz Antônio dos Santos; Silva, Acácio de Paula (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to evaluate the agronomic performance of 140 cacao (Theobroma cacao L.) accessions of different origins. From 2002 to 2005, the accessions were evaluated for yield components and field-resistance components to witches' broom and fruit borer. Annual data computed per harvests and accession were analyzed by descriptive, linear correlation and variance analyses in factorial experiment and mean tests. All evaluated traits had expressive variability. The accessions CAB 9, 13, 40, 218, 226, 417 e 452 were outstanding for witches' broom and fruit borer resistance and yield performance. The identification of witches' broom tolerant accessions increased the gene sources for utilization in plant breeding for horizontal resistance to Moniliophthora perniciosa.